Impact of Viral Load in Polyoma-BK Virus Viremia on Histologic Findings in Late Protocol Biopsy in Kidney Transplant Recipients. (July 2018) - Reischig, Tomas; Kacer, Martin; Hes, Ondrej; Machova, Jana; Bouda, Mirko
Abstract : Background: Polyoma-BK virus associated nephropathy (PVAN) progress from interstitial nephritis to advanced interstitial fibrosis and tubular atrophy (IF/TA) with premature graft loss. Systematic surveillance for asymptomatic BK virus (BKV) viremia with pre-emptive reduction of immunosuppression is the only proved preventive strategy to reduce the risk of PVAN. However, the safe level of BKV viremia without risk of IFTA development is not established. Materials and Methods: In prospective cohort of kidney transplant recipients, we assessed the impact of BKV viremia on the incidence of moderate-to-severe IF/TA in protocol biopsy at 36 months. Except for cases of graft dysfunction plasma PCR for BKV DNA was monitored monthly during first 6 months and at months 9, 12, 15, 18, 21, 24, and 36 thereafter. Lower detection limit was 50 copies/mL. High grade BKV viremia was defined as ≥10, 000 copies/mL. Results: A total of 207 patients transplanted from Oct 2003 through Mar 2012 were included nd followed for 5 years. Within 36 months of transplantation, BKV viremia developed in 57 (28%) patients; 10 (5%) patients suffered from biopsy-proven PVAN. High grade BKV viremia (median viral load, 27, 200 copies/mL) occurred in 10/57 (18%) patients with low grade (median viral load, 100 copies/mL, P<0.001) in 35/57 (61%). In 12 patients BKV viral load could not be determined. The incidence of PVAN was significantly higher in high grade compared to low grade BKV viremia (70% vs. 6%, P<0.001). In late protocol biopsy the incidence of moderate-to-severe IFTA was comparable in patients with BKV viremia compared to patients without BKV (31% vs. 25%, P=0.409); however, after stratification by viral load, high grade BKV viremia was associated with increased incidence of moderate-to-severe IF/TA (71%, P=0.007) while the impact of low grade BKV viremia was negligible (22%, P=0.776). Overall graft survival at 5 years was similar in BKV viremia and patients without BKV (81% vs 87%, P=0.215). Only patients with PVAN showed lower graft survival (50% vs. 87%, P<0.001). Conclusions: Low grade BKV viremia did not increase the risk of advanced IF/TA at 3 years after kidney transplantation. High grade BKV viremia is associated with PVAN development and resulted in high incidence of moderate-to-severe IF/TA.